ANTI-INFLAMMATORY AND AMYLASE INHIBITORY PROPERTIES OF INDIAN EDIBLE MACROFUNGI OF INDIAN EDIBLE MACROFUNGI OF INDIAN EDIBLE MACROFUNGI Dacryopinax spathularia Dacryopinax spathularia (Schwein) (Schwein) AND Schizophyllum commune Schizophyllum commune (Fr - AND M. P. SINHA, AMAR KUMAR, SUKUMAR DANDAPAT , MANOJ KUMAR (The Bioscan, 2018)
The present study deals with the two edible macrofungi Viz. D. spathularia and S. commune, which are subjected to phytochemical screening and their extracts have been tested for their anti-inflammatory and amylase-inhibitory impact. Results showed that D. spathularia extract shows 14.01% inhibition of Hyaluronidase enzyme at 100 microgram concentration, whereas S. commune extract shows 15.76% hyaluronidase inhibition at the same cocentration. In addition to these medicinal properties, extracts from both macrofungi were tested to have amylase inhibition properties, which is of great importance in the field of alternative medicines for Diabetes melitus. At 1000 microgram concentration the D. spathularia extract is found to have 38.24% inhibition of amylase, whereas S. commune extract is found to have 48.19% amylase inhibition activity.